ESIPT-AIE active Schiff base based on 2-(2′-hydroxyphenyl)benzo-thiazole applied as multi-functional fluorescent chemosensors. Issue 11 (26th February 2021) - Zheng, Han-Wen; Kang, Yang; Wu, Min; Liang, Qiong-Fang; Zheng, Jian-Quan; Zheng, Xiang-Jun; Jin, Lin-Pei
Abstract : For AIE-ESIPT-active compounds, their steric hindrance, rotatable aromatic rings and isomerism should be considered when sensing metal ions. Abstract : Three AIE (aggregation-induced emission)-ESIPT (excited-state intramolecular proton transfer) active 2-(2-hydroxyphenyl)benzothiazole derivatives, HL 1, HL 2 and HL 3 with one, two and three rotatable phenyl groups, were obtained and characterized. Their AIE properties in THF/HEPES solution were investigated in detail. HL 2 shows the best AIE performance with 71-fold fluorescence enhancement, while HL 3 only shows a 9-fold enhancement. With the AIE property, HL 1 and HL 2 could act as fluorescence chemosensors to detect Cu 2+ ions via the "turn off" mode in THF/HEPES media. With the ESIPT property, HL 1 and HL 2 could also detect Zn 2+ ions via the "turn on" mode in EtOH/HEPES media. During the detection process, both demonstrate rapid response and high contrast before and after the addition of metal ions. The species formed in the detection system were investigated. The results of X-ray single-crystal diffraction confirm that Zn 2+ is coordinated with the oxygen atom and Schiff base nitrogen atom instead of the benzothiazole nitrogen atom in the tetrahedron geometry. Moreover, the chemosensors were successfully constructed into handy fluorescence test papers for Cu 2+ and Zn 2+ detection.